2006
DOI: 10.1108/14720700610689577
|View full text |Cite
|
Sign up to set email alerts
|

The impact of higher education on students' and young managers' perception of companies and CSR: an exploratory analysis

Abstract: Purpose -The purpose of this article is to analyse the impact of higher education on students' and young managers' perception of companies and corporate social responsibility (CSR).Design/methodology/approach -The research is based on an electronic questionnaire for students and alumni of different institutions of higher education in Nantes (France). The textual analysis software ALCESTE enabled interpretion of the answers to the open-ended questions. Concerning the closed questions, analyses by simple sort an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 6 publications
7
50
3
Order By: Relevance
“…Thus, we can state that a higher level of education is a key factor that supports CSR development in practice. Other studies [22] support our conclusion that CSR-educated individuals have a better attitude toward CSR and that CSR education can have multiple implications on curriculum developing, public policies implications and for employing multinational companies [20]. Even in the case of educational institutions that develop and teach CSR-related management tools, there is still a need to integrate CSR into the organisational culture [20].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, we can state that a higher level of education is a key factor that supports CSR development in practice. Other studies [22] support our conclusion that CSR-educated individuals have a better attitude toward CSR and that CSR education can have multiple implications on curriculum developing, public policies implications and for employing multinational companies [20]. Even in the case of educational institutions that develop and teach CSR-related management tools, there is still a need to integrate CSR into the organisational culture [20].…”
Section: Discussionsupporting
confidence: 66%
“…Sobczak, Debucquet and Havard [20] in an exploratory study examined the impact of the French educational system on the CSR-related perceptions of students and young managers (alumni). The authors underlined that there is a need for higher education institutions to integrate CSR into their culture.…”
Section: Perceptions Of Business Students Toward Csrmentioning
confidence: 99%
“…The findings are more accurate than those obtained by other researchers who focused on a single higher education course (Rama et al, 2000;Sobczak et al, 2006;Wang & Juslin, 2011, 2012, more specifically bachelor of accounting, with findings extended to the whole area of business management. That procedure has been strongly criticized.…”
Section: Values Versus Csr: Model and Hypothesissupporting
confidence: 56%
“…Although research on the relationship between social demographics and value structures can be found in the literature (Wang & Juslin, 2012), few studies have empirically analyzed the influence of the framework of human values on the perception of corporate social responsibility (CSR) in the context of higher education (Rama, Ravenscroft, Wolcott, & Zlotkowski, 2000;Sobczak, Debucquet, & Havard, 2006;Weber, Weber, Sleeper, & Schneider, 2004;Weber & Glyptis, 2000;Wong, Long, & Elankumaran, 2010). Despite the scarcity of studies, consumer perception of CSR can be an important determinant of the success of CSR practices in any organization.…”
Section: Introductionmentioning
confidence: 99%
“…The fact whether the issue of the social aspect of conducting the business will function at a management level depends on the perception of its importance. Therefore, a natural consequence seems to be to introduce the courses dealing with corporate social responsibility into teaching programs at universities (Sobczak et al 2006). This issue is an argument for discussion for many researchers (MacVaugh, Norton 2012;Stubbs 2013;Savelyeva, McKenna 2011).…”
Section: Introductionmentioning
confidence: 99%